2016
DOI: 10.1038/ng.3746
|View full text |Cite
|
Sign up to set email alerts
|

SMARCB1-mediated SWI/SNF complex function is essential for enhancer regulation

Abstract: SMARCB1 (SNF5/INI1/BAF47), a core subunit of the SWI/SNF (BAF) chromatin remodeling complex1,2, is inactivated in nearly all pediatric rhabdoid tumors3–5. These aggressive cancers are among the most genomically stable6–8, suggesting an epigenetic mechanism by which SMARCB1 loss drives transformation. Here, we show that despite indistinguishable mutational landscapes, human rhabdoid tumors show distinct enhancer H3K27ac signatures, which reveal remnants of differentiation programs. We show that SMARCB1 is requi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
310
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 289 publications
(341 citation statements)
references
References 39 publications
24
310
6
1
Order By: Relevance
“…SMARCB1 deletion results in reduced occupancy of SWI/SNF complex at standard enhancers of differentiation‐specific genes and occupancy at SE of genes associated with lineage specificity and pluripotency . Our data show that MYC chromatin occupancy at differentiation and pluripotency gene promoters is altered in SMARCB1 deleted cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…SMARCB1 deletion results in reduced occupancy of SWI/SNF complex at standard enhancers of differentiation‐specific genes and occupancy at SE of genes associated with lineage specificity and pluripotency . Our data show that MYC chromatin occupancy at differentiation and pluripotency gene promoters is altered in SMARCB1 deleted cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al . suggest that aberrant SWI/SNF complexes abnormally activate pluripotency transcription factors such as SALL4 and SOX2 through their SE . Here we show that another pluripotency‐associated transcription factor, the c‐ MYC oncogene (henceforth MYC ), is a critical regulator of ATRT malignant behavior in the context of SMARCB1 deletion.…”
Section: Introductionmentioning
confidence: 99%
“…The SWI/SNF complex facilitates the unwinding of heterochromatin through an ATP-dependent manner. These complexes are impaired in their targeting to DNA when SMARCB1 is absent resulting in a loss of the complex at enhancers that maintain differentiation and remaining at super-enhancers that promote survival (Wang et al, 2017). These studies have demonstrated how crucial epigenetic integrity is at enhancer regions and may point to universal epigenetic means of reversing the state of differentiation, which is often associated with malignant disease.…”
Section: Sarcoma Research–the Present Past and Futurementioning
confidence: 99%
“…To investigate the impact of SMARCB1 inactivation on SWI/SNF complex assembly and targeting, Roberts, Bernstein, Park and colleagues 5 examined the genome-wide localization of SWI/SNF complex in SMARCB1-wildtype and deficient rhabdoid tumors and cell lines. In addition to gene promoters, they found that a substantial portion of SWI/SNF complexes were recruited to enhancers and so-called ‘super-enhancers’ (clusters of active enhancers) in SMARCB1-wildtype cells.…”
Section: ‘Remodeling’ the Enhancersmentioning
confidence: 99%
“…Mutations, translocations and deletions involving various subunits of SWI/SNF complex were found in ∼20% of human tumors, making the complex as one of the most commonly affected target in cancer 4 . In this issue, four research articles offer novel insights into the mechanisms by which SWI/SNF complex alterations lead to defective complex assembly and recruitment, abnormal gene silencing and tumor development 5-8 . Importantly, these mechanisms help explain the preclinical efficacies of several therapeutic approaches developed to target SWI/SNF-mutated tumors.…”
mentioning
confidence: 99%